Utility of tissue elafin as an immunohistochemical marker for diagnosis of acute skin graft‐versus‐host disease: a pilot study. (1st March 2019) - Mahabal, G. D.; George, L.; Peter, D.; Bindra, M.; Thomas, M.; Srivastava, A.; Mathews, V.; George, B.; Pulimood, S. A.
Summary: Background: The skin is the most common organ involved in acute graft‐versus‐host disease (GvHD). Because histopathology has limited utility in ruling out clinical mimics of acute skin GvHD, more accurate diagnostic techniques are required. Aim: To evaluate the utility of elafin expression in skin by immunohistochemistry (IHC) for accurate diagnosis of acute skin GvHD. Methods: Consecutive allogeneic haematopoietic stem cell transplant (HSCT) recipients during a 6‐month period who developed rash within the first 100 days post‐transplant were recruited. Skin biopsies were taken on the day the rash developed. IHC for epidermal elafin was performed and interpreted by a pathologist blinded to the histopathological diagnosis. Staining of ≥ 50% of epidermis was considered positive. Final diagnosis of the rash was assigned using clinical features supported by histopathology. The accuracy of elafin IHC in predicting the final diagnosis of acute GvHD was evaluated. Results: In total, 23 patients (20 male, 3 female; median age 16 years, range 3–53 years) with 27 episodes of skin rash were recruited. Skin rash post‐HSCT occurred at a median of 20 days (range 5–45 days). A diagnosis of GvHD was made in 16 episodes (59.26%) while the remaining 11 episodes (40.74%) were judged to be non‐GvHD rash. Elafin IHC was positive in all patients with GvHD. Of the 11 episodes of non‐GvHD rash, elafin was negative in 8. Thus, the sensitivity and specificity of elafin IHC for predicting acute skin GvHD was 100% and 75%, respectively. Conclusion: Tissue elafin is a useful immunohistochemical marker for acute skin GvHD. However, larger studies are needed to validate these results.